Functionally generated amalgam stops for single complete denture: A case report - Pravinkumar G Patil; Rambhau D Parkhedkar (Wolters Kluwer Medknow Publications, 2009)
Single complete denture opposing natural dentition is a common occurrence in clinical practice. This article reports a case of a single complete denture with a technique of occlusal refinement by func-tionally generated amalgam stops condensed in prepared resin teeth after initial balancing of the den-ture with semi-adjustable articulator. This technique provides intimacy of contact in all excursions by carving the amalgam in plastic stage. Amalgam stops improve the efficiency of the resin teeth. Den-tures fabricated using this technique require fewer and simpler post-insertion adjustments.